PERAN PERUSAHAAN KELUARGA, DIVERSIFIKASI PERUSAHAAN DAN LEVERAGE DALAM MANAJEMEN LABA - Damara, Devina; Lembut, Putu Indrajaya; Oktariani, Fitri (Ma Chung Press, 2023)
This study aims to prove the relationship between family firms, company diversification and leverage on earnings management with good corporate governance as a moderating variable. Earnings management is proxied by using discretionary accruals. The main dependent variables in this study are family companies, company diversification and leverage. Researchers also conducted different tests on the leverage variable before and during Covid19. The sample in this study is a family company in the manufacturing sector that is listed on the IDX in the 2017-2021 period. The different test samples in this study used 2018-2019 before Covid19 and 2020-2021 during Covid19. The number of samples in this study were 14 companies. The research hypothesis was tested using Partial Least Square Structural Equation Modeling with SmartPLS 4.0 software and SPSS. This study shows that there is no significant relationship between family firms and leverage with earnings management. The diversification variable has a negative effect on earnings management. Good corporate governance variables are not able to weaken the influence of family firms, corporate diversification and leverage on earnings management. Meanwhile, there was no difference before and during Covid-19 in terms of leverage.